VIRAL DISEASES IN CHILDREN AND ITS CONSEQUENCES - Rahmonova Gulnoza Rahimjonovna; Qo'chqarov Baxromjon Vohidjon o'g'li; Isroilov Asilbek Muxiddin o'g'li; Isroilova Mohinur Umidjon qizi (Western European Studies, 2024)
This article explores the various viral diseases that affect children, examining their short-term and long-term consequences. It provides a comprehensive analysis of the current literature, outlines the methodologies used in recent studies, presents results, and discusses the implications for future research and public health strategies.
Keywords: Viral diseases; children; pediatric health